Fulleranes The Hydrogenated Fullerenes - Cataldo, Franco; Iglesias-Groth, Susana; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Fulleranes are a special class of carbon molecules derived from fullerenes whose double bonds are partially or at least theoretically fully saturated by hydrogen. The hydrogenation changes the chemical properties of fullerenes which can become susceptible to substitution reactions as opposed to addition reactions to the double bonds (present in common fullerenes). One of the most intriguing aspects of fulleranes is the fact that they have been thought to exist in the interstellar medium or even in certain circumstellar media. The reasoning is quite simple: if fullerenes can be formed in the interstellar or better in the circumstellar medium, then they should undergo a simple hydrogenation reaction because of the ubiquitous presence of hydrogen in the universe. There is therefore a need not only to synthesize fulleranes in order to study their properties but also to study their infrared and electronic absorption spectra. Such spectra are used in the search for these molecules in the interstellar medium and around certain promising carbon-rich stars. Many efforts have been made by chemists and chemical physicists to synthesize these molecules at different degrees of hydrogenation and to record their spectra. Thus, Fulleranes: The Hydrogenated Fullerenes presents the state of the art research, synthesis and properties of these molecules; astrophysicists and astrochemists detail their expectations regarding the presence of these molecules in space. Fulleranes: The Hydrogenated Fullerenes is written for researchers, postgraduates, and advanced undergraduates in organic synthetic chemistry, physical chemistry, and astrophysics.
Fulleranes and Carbon Nanostructures in the Interstellar Medium -- Infrared and Ultraviolet Spectra of Fulleranes: HREELS Studies and Implications for the Interstellar Medium -- The Potential Role Played by the Fullerene-Like Structures of Interstellar Carbon Dust in the Formation of Molecular Hydrogen in Space -- Thermodynamic Properties of Fullerene Hydrides C60H2n and Equilibria of Their Reactions -- Fulleranes by Direct Reaction with Hydrogen Gas at Elevated Conditions -- Chemical Methods to Prepare [60]Fulleranes -- Synthesis, Stability and Spectroscopy of Perdeuterofulleranes: C60D36 and C70D38 Evidences of Isotope Effects -- Isotope Effect in the UV Photolysis of Hydrogenated and Perdeuterated Fulleranes -- Characterization of Hydrogenated Fullerenes by NMR Spectroscopy -- Low Temperature Infrared Spectroscopy of C60 and C70 Fullerenes and Fullerane C60H18 -- High-Pressure Hydrogenated Carbon Nanostructures -- Topological Modeling of C60H36 Hydrides.
Keywords: Chemistry; Chemistry, Organic; Chemistry, Physical organic; Chemistry; Organic Chemistry; Astrophysics and Astroparticles; Physical Chemistry